Linguistic diversity and teaching - Commins, Nancy L. (Reflective teaching and the social conditions of schooling., 2005)
Divided into three parts, this book provides a context for reflection regarding the complex issues surrounding new English learners in schools. The text addresses these issues through conversations among experts, practitioners, and readers that are informed by representative case studies and by a range of theoretical approaches.